A proposal to build a reading center in Barangay Diit, Tacloban City Leyte (Region VIII) - Vergara, Lucille D. (Institute of Library and Information Science, University of the Philippines Diliman, 2002)
The reading center is going to be established for the residents of Brgy. Diit, Tacloban City.The reading center will be located at the Brgy. Hall. Its collections will focus on agriculture, family health, home economics, young adult's literature and children's literature. It will offer services such as lending reading materials, story-telling for children and a movie-viewing program for the adults in the community.